The Beargrass Story: Utilizing Social Science to Evaluate and Learn from the "Watershed Approach". (2nd September 2019) - Church, Sarah P.; Babin, Nicholas; Bentlage, Belyna; Dunn, Michael; Ulrich‐Schad, Jessica D.; Ranjan, Pranay; Magner, Joe; McLellan, Eileen; Stephan, Susi; Tomer, Mark D.; Prokopy, Linda S.
Abstract: This paper presents the case of a voluntary watershed project that addressed the need for improving water quality by reducing agricultural nutrient loss. The Beargrass Creek Watershed Approach Project in Wabash County, Indiana aimed to demonstrate that it is possible to achieve ambitious water quality goals and maximize the effectiveness of conservation funding through locally‐led efforts that bring together multiple stakeholders throughout the process. The project focused on implementing the "right practices" in the "right places" through a goal‐oriented, science‐based, and locally‐adapted approach to voluntary conservation. We examine and evaluate all three phases of the project and discuss successes and lessons learned from the point of view of both agricultural producers and agency staff from the local Soil and Water Conservation District and the Natural Resources Conservation Service.